Ketepatan dan Kesalahan Persepsi Konsumen Terhadap Pionir dan Pemimpin Pasar - Ervina Triandewi; Fandy Tjiptono (Forum Manajemen Indonesia (FMI), 2014)
Pioneer and market leader positions are sources of unique differentiation and competitive advantages. Empirical studies have suggested that pioneer or leader brands tend to be evaluated more favourably than follower brands. However, consumers’ ability to recognize pioneer or market leader brands accurately is limited. In fact, their perception and misperception of market pioneership and market leadership may affect their beliefs and decision making processes. The present study aims to investigate consumers’ ability to identify pioneer and market leader brands across three product categories representing high-tech products, low involvement goods, and services. It also analyzes consumer evaluation, attitude, and purchase intention of brands perceived as market leaders, pioneers, and followers. Data were collected using self-administered questionnaires from a convenient sample of 225 college students in Daerah Istimewa Yogyakarta (DIY). Four hypotheses adapted from Kamins et al. (2003) were examined using F-tests, post-hoc tests with Tukey and Duncan Multiple Range Test (DMRT), and pairwise t-tests. The results indicate that consumers have lower ability to recognize pioneer brands than market leader brands (70.89% versus 29.95%). In general, consumers have more favourable evaluation, attitude, and purchase intention of brands perceived as pioneers or market leaders than those perceived as followers. Keywords: Market pioneer, market leader, pioneer advantages, misperception, follower.